Cranial unifocal langerhans cell histiocytosis in a female child: a difficult case with S-100 and CD1a immunonegativity - Soeripto, J Bras, Hanggoro Tri Rinonce Sagiri Mangunsudirdjo (Journal of the Medical Sciences (Berkala Ilmu Kedokteran), 2011)
A 13-years old female child was carried to Dr. Sardjito General Hospital, Yogyakarta by her mother with chiefcomplaint of a mass on her forehead. Since eight months prior to her visiting, she had a mass on her forehead whichbecame larger slowly without tenderness and had no fever. Clinical examination revealed a well circumscribedmass, 3 cm in diameter, fixed, with rubbery consistency. The skull X-ray revealed a punch out lesion in frontal bone.The head CT scanning revealed a destruction of frontal bone. Clinical diagnosis of dermoid cyst was determined,excision and curettage was performed. Gross examination showed 2.5 cc fragmented tissue, brownish yellow, withrubbery consistency. A diagnosis of benign histiocytosis (Langerhans cell histiocytosis or non-Langerhans cellhistiocytosis) of frontal bone was determined based on morphological and immunohistochemical examination. Theaim of this presented article was to report a rare case of cranial unifocal Langerhans cell histiocytosis in a femalechild with S-100 and CD1a immunonegativity, and to discuss how to determine its diagnosis based on literaturereview.Key words: Langerhans cell histiocytosis - juvenile xanthogranuloma â reticulohistiocytoma - eosinophilic granulomaâ S100 â CD1a